Congenital cataract: An ocular manifestation of classical homocystinuria. Issue 9 (2nd August 2021) - Saba, Neelam; Irshad, Saba
Abstract: Background: Homocystinuria is an autosomal recessive metabolic disorder occurring due to the defects in cystathionine‐β‐synthase enzyme. The study was carried out to investigate a Pakistani family presenting bilateral congenital cataract with symptoms of classical homocystinuria at LRBT Free Eye Hospital, Lahore, Pakistan. Methods: Three affected individuals of the family presented skeletal deformations, intellectual disability, speech delay, and myopia with bilateral congenital cataract. Genetic analysis on DNA samples from affected individuals was done through whole exome sequencing to identify underlying genetic variant causing disease phenotypes in the family. In silico analysis was done to predict the effect of variation on the structure of mutant protein. Results: A missense allelic variant (NM_000071.3: c.253G>A) of the CBS gene was revealed which may affect the catalytic activity of the substituted (NP_000062.1: p.G85R) protein by disrupting the folding of the enzymatic protein. High levels of homocysteine were observed in the plasma of affected individuals. This is the first report of this genetic variant from Pakistan causing homocystinuria and congenital cataract in association. Conclusion: This variant was reported first time in association with congenital cataract instead of ectopia lentis. Congenital cataract was developed secondarily in these patients and provided a clue for the early diagnosis of metabolic disorders like homocystinuria to prevent further complications and morbidity. Abstract : This study was done to identify the genetic cause of CC in a Pakistani family. Through WES, a missense SNP of the CBS gene responsible for classical homocystinuria was revealed, which developed CC secondarily in the patients.